Accounting Theory Formulation as a TOOL for Enhancing International Harmonization of Accounting Standards (JOURNAL OF INNOVATIVE RESEARCH IN MANAGEMENT AND HUMANITIES, 2011)
Literature reviews show that accounting is practiced within an implicittheoretical framework composed of principles and practices that have been accepted by theprofession because of their alleged usefulness and logic, it is increasingly difficult toconvince the specialist of other disciplines merely by saying “this has been the practice”.This difficulty is further compounded as accountants across the globe adopt differentaccounting standards that best suit the economic climate in which they operate. This paperfocuses on the accounting theory formulation as tool to enhance uniform accountingstandards. The traditional and new approaches to accounting theory formulation wasdiscussed and the main recommendations were that a set of universal accounting standardshould be developed to back already existing international accounting standard andharmonization of all local and international standards so that there will be a common basisof financial reporting globally. The theories should be adhered to by Practicing Accountantto avoid public scandal and confusion.
Keywords: accounting standard, financial reporting, harmonization, Economic reality, economic consequences